The Level of Emotional Sensitivity Among Students With Learning Disabilities - Awais, Buthiana Elias; Alkinani, Reem Abdallah; Zaitoun, Musa Suleiman Abu; Abu Issa, Abd Alhameed Mahmoud; Al-Rub, Mohammaed Omar Abu (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the level of emotional sensitivity among students with learning disabilities in the Hashemite Kingdom of Jordan, and followed the descriptive approach, where the sample of the study consisted of (480) students. They were randomized, and the researcher used the emotional sensitivity scale. The study found that the level of emotional sensitivity is moderate. The results of the study showed that there were significant differences in the level of emotional sensitivity among students with learning disabilities due to sex variables for the benefit of females and in the academic level for the benefit of fourth, fifth and sixth graders. According to the study results, a set of recommendations and future studies were suggested.